Analysis Of Transformational Leadership Style And Competencies On Employee Performance With Organizational Culture As An Intervening Variable On Pt. Pln (Persero) UP2D Sumut - Rahmat Hidayat Harahap; Elfitra Desy Surya (Utan Kayu Publishing, 2025)
This research aims to analyze the influence of transformational leadership style and employee competencies on employee performance, with organizational culture acting as an intervening variable at PT. PLN (Persero) UP2D North Sumatra. The study is motivated by the strategic role of leadership and competencies in enhancing organizational performance within the state-owned electricity sector, especially in adapting to dynamic environmental and technological changes. A quantitative approach was used with data collected through questionnaires distributed to 100 employees using purposive sampling. Structural Equation Modeling (SEM) with the SmartPLS application was utilized to test the proposed hypotheses. The findings show that transformational leadership style and competencies have a significant positive effect on employee performance. Furthermore, organizational culture partially mediates the relationship between both transformational leadership and competencies on employee performance. This indicates that a strong organizational culture enhances the positive effects of leadership and competencies on performance outcomes. The study contributes to the theoretical development of human resource management and provides practical implications for PT. PLN (Persero) in strengthening leadership and cultural transformation to optimize employee performance.